High Ficolin-3 Level at the Time of Transplantation Is an Independent Risk Factor for Graft Loss in Kidney Transplant Recipients. Issue 4 (April 2015) - Smedbråten, Yuliya V.; Sagedal, Solbjørg; Mjøen, Geir; Hartmann, Anders; Fagerland, Morten W.; Rollag, Halvor; Mollnes, Tom Eirik; Thiel, Steffen
<x xml:space="preserve">Abstract</x> Background Recent studies have shown that activation of the complement system may be associated with long-term graft function. The aim of this retrospective study was to assess the impact of the pattern recognition molecules of the lectin pathway on long-term graft survival after kidney transplantation. Methods Patients transplanted in 2000 to 2001 were included. Mannose-binding lectin, Ficolin-1, and Ficolin-3 were measured in serum at the time of transplantation. Data on death-censored graft loss were obtained from the Norwegian Renal Registry. Competing risks regression was used to investigate the association between time to graft loss and the explanatory variables. The variables were: high Ficolin-3 (upper quartile, ≥33.3 μg/mL) versus low Ficolin-3 (<33.3 μg/mL), acute rejection (time-dependent), age, basiliximab induction, sex, donor age, human leukocyte antigen mismatches, human leukocyte antigen antibodies, cold ischemia time, living donor, and preemptive transplantation. Results A total of 382 patients with a median follow-up of 9.8 years were included. Sixty-six patients (17%) had death-censored graft loss, and 116 (30%) patients died. In a final competing risks model, high Ficolin-3 (subhazard ratio [SHR] = 1.95, P = 0.009), acute rejection (one vs. none) (SHR = 1.93, P = 0.033), acute rejection (two vs. none) (SHR = 5.45, P < 0.001), and age (SHR = 0.98, P = 0.006) were associated with death-censored graft loss. Basiliximab induction was associated with improved graft survival (SHR = 0.50, P = 0.016). No associations between mannose-binding lectin or Ficolin-1 and graft loss were found. Conclusion High Ficolin-3 level at the time of transplantation was an independent significant risk factor for shorter graft survival, even when adjusted for other covariates.